Older people's diet-related beliefs and behaviours: Intervention implications - Pettigrew, S.; Pescud, M.; Donovan, Robert (Wiley-Blackwell Publishing Asia, 2012)
Aim: Health promotion campaigns in Australia have not addressed the needs of an ageing population for nutrition related information. Such campaigns would need to focus on those middle-aged and older to ensure that individuals are aware of appropriate dietary behaviours to sustain them into older age. The present study explored the diet-related beliefs and behaviours of mature adults to inform future healthy eating interventions targeting this group. Methods: An inductive, qualitative approach was used to generate information relating to mature adults’ diet related beliefs and behaviours. Twenty individual interviews and 12 focus groups were conducted with 111 Western Australians aged 40+ years. Data were collected from individuals residing in metropolitan and regional areas. Data coding and analysis were conducted with the use of NVivo7 software (QSR International, Doncaster, Victoria, Australia). Results: The consistent findings across age groups and geographical locations suggest that mature adults may not be aware of the implications of ageing on changing dietary needs, and in particular they may lack general knowledge of current guidelines for specific nutrients such as salt and alcohol. Information relating to appropriate serving sizes of different foods may also be useful for members of this segment. Conclusions: While further research is required to support these qualitative findings, it appears that diet-related information may be more readily accepted by mature adults if it is presented as preventing future deterioration rather than improving current health states.